2014
DOI: 10.1007/s11356-014-3512-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exposure to O3, NO2, and SO2 on chronic obstructive pulmonary disease hospitalizations in Tabriz, Iran

Abstract: Air pollution in cities is a serious environmental problem especially in the developing countries. We examined the associations between gaseous pollutants and hospitalizations for chronic obstructive pulmonary diseases (COPD) among people living in Tabriz, a city in north western of Iran. We used the approach proposed by the World Health Organization (WHO) using the AirQ 2.2.3 software developed by the WHO European Center for Environment and Health, Bilthoven Division. To assess human exposure and health effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 23 publications
5
31
2
4
Order By: Relevance
“…Both of these two gaseous pollutants caused an increased risk of COPD significantly (RR, 95% CI): 1.04, (1.03, 1.06); and 1.03, (1.01, 1.04). One study reported that every 10 μg/m 3 increase of O 3 and NO 2 would result in 0.58% and 0.38% increment in the COPD risk, respectively 33. In addition, exposure to SO 2 and CO showed weaker associations with COPD in the present study, which was consistent with a previous study.…”
Section: Discussionsupporting
confidence: 88%
“…Both of these two gaseous pollutants caused an increased risk of COPD significantly (RR, 95% CI): 1.04, (1.03, 1.06); and 1.03, (1.01, 1.04). One study reported that every 10 μg/m 3 increase of O 3 and NO 2 would result in 0.58% and 0.38% increment in the COPD risk, respectively 33. In addition, exposure to SO 2 and CO showed weaker associations with COPD in the present study, which was consistent with a previous study.…”
Section: Discussionsupporting
confidence: 88%
“…This software has been employed in a variety of past studies (Fattore et al, 2011; Naddafi et al, 2012; Gharehchahi et al, 2013; Gholampour et al, 2014; Ghozikali et al, 2015; Goudarzi et al, 2015; Marzouni et al, 2016) and allows for calculations of the potential impact of exposure to air pollutants in specific urban areas during a specific time period. The method is based on quantification of ‘attributable proportion (AP)’, which is the fraction of a given health outcome in a population due to exposure to a specific pollutant with the assumption of a proven causal relationship between exposure and the health outcome.…”
Section: Methodsmentioning
confidence: 99%
“…In 2009, in Tabriz city, Iran Ghozikali et al estimated the chronic obstructive pulmonary disease hospitalizations attributed to SO 2 (Ghozikali et al 2015a). In another study in Detroit, USA, Lipmann et al reported meaningful association between sulfur dioxide level and health effects on human (Lippmann et al 2000).…”
Section: Introductionmentioning
confidence: 99%